Associations Between Home Dampness-related Indicators and Eczema among Preschool Children in Shanghai, China. (2015) - Cai, Jiao; Huang, Chen; Liu, Wei; Hu, Yu; Zou, Zhijun
Abstract: In recent years, prevalence of eczema has been increasing among preschool children in China. It's urgent to find associated factors. On basis of 13, 335 questionnaires from parents or guardians for 4-6 year-old children (response rate 85.3%) in a cross-sectional study from April 2011 to April 2012 in Shanghai, the associations between home dampness related indicators and the prevalence of childhood eczema was investigated. There were 7.8%, 15.3%, 42.1%, 55.7%, and 30.7% of the surveyed residences who had visible mold spots, visible damp stains, damp clothing and/or bedding, water damage, condensation on window in winter, and moldy odor (six home dampness-related indicators), respectively. The prevalence of eczema (ever) and eczema (in the past 12 months) was 22.9% and 13.2%, respectively. These home dampness indicators had significant and strong associations with the increased risk of childhood eczema. With regard to the same indicators, the increased risk of eczema in girls was higher than in boys. Total numbers of home dampness-related indicators had notable dose-response relationships with the prevalence of childhood eczema. In conclusion, home dampness-related exposures are strong risk factors for childhood eczema.